The role of self-efficacy, motivation, and perceived support of students' basic psychological needs in academic achievement - Basileo, Lindsey D.; Otto, Barbara; Lyons, Merewyn; Vannini, Natalie; Toth, Michael D. (Frontiers in Education, 2024)
Former research has highlighted the relevance of basic psychological need (BPN) satisfaction for students' academic motivation and achievement. However, the specific role of self-efficacy in this relationship has been neglected. Using survey response data from a sample of 2,359 German middle school students in 35 schools, we employed Hierarchical Linear Modeling to investigate the role of teacher support for students' perceived BPN, academic self-efficacy, and autonomous and controlled motivation on student achievement in two subjects (mathematics, German). We found that selfefficacy had the largest relationship with achievement and it mediated the effect of autonomous motivation on grades while controlled motivation had a small and statistically significant, negative relationship regardless of self-efficacy. Support of students' perceived BPN had a postive statistically signficant association with autonomous motivation. Motivation and self-efficacy also mediated perceived BPN support and achievement. Self-efficacy had a statistically signficant association and had a reciprocal relationship with both autonomous and controlled motivation. The findings indicate that self-efficacy plays a major role in the relationships among perceived BPN support, motivation, and academic achievement, and highlight the importance of supporting student self-efficacy in academic settings.